Peningkatan Hasil Belajar Matematika Dalam Tugasku Sehari - hari di Sekolah Menggunakan Power Point Pada Peserta Didik Kelas II SDN Karanganyar 01 - Sri Mulyati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in thematic learning in grade II SD. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 14 grade students of SDN Karanganyar 01 in the 2020/2021 academic year. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the use of learning powerpoint media can improve student learning outcomes in the subject matter of Theme 3 Sub Theme 2 Learning 1 in class II Karanganyar 01 Elementary School for the 2020/2021 school year as evidenced by the percentage of learning outcomes in cycle I by 70% to 90% in the cycle II and becomes 100% in cycle III